2023
DOI: 10.1038/s41598-023-47643-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of multimodal cues in second language comprehension

Ye Zhang,
Rong Ding,
Diego Frassinelli
et al.

Abstract: In face-to-face communication, multimodal cues such as prosody, gestures, and mouth movements can play a crucial role in language processing. While several studies have addressed how these cues contribute to native (L1) language processing, their impact on non-native (L2) comprehension is largely unknown. Comprehension of naturalistic language by L2 comprehenders may be supported by the presence of (at least some) multimodal cues, as these provide correlated and convergent information that may aid linguistic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Studies carried out by various researchers have shown that speech and gestures share a cognitive stage of processing in language understanding as they do in language production (Arbona et al, 2023;Goldin-Meadow & Alibali, 2013;Zhang et al, 2023). By sharing a common neural system in the brain with the use of speech, Vol.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies carried out by various researchers have shown that speech and gestures share a cognitive stage of processing in language understanding as they do in language production (Arbona et al, 2023;Goldin-Meadow & Alibali, 2013;Zhang et al, 2023). By sharing a common neural system in the brain with the use of speech, Vol.…”
Section: Literature Reviewmentioning
confidence: 99%